PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN 2 RARANG - Widia Hakiki, Baiq; Karma, Nyoman; Husniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of the problem-based learning model on the learning outcomes of science learning outcomes of fourth grade students of SDN 2 Rarang in the 2023/2024 school year. This type of research is a quasi-experimental design with posttest only control group design which is a form of experimental research method. The population in this study were fourth grade students of SD Negeri 2 Rarang in the 2023/2024 academic year consisting of 2 classes, namely IV-A and IV-B classes. The sampling technique is a saturated sample or total sampling. The samples of this study were students of class IV (A) as an experimental group using a problem-based learning model and class IV (B) as a control group using a conventional learning model. Data collection techniques in this study were tests and observations. The instrument used in this study was a student learning outcomes test sheet (posttest) on energy source material. The data analysis used was t test and effect size test. Based on the results of data analysis of posttest values using the t test where the t_hitung = 4.825> t_table = 2.001 with a significant level of 5%, so that H_0 is rejected and the effect size test is obtained d = 1.268 (High Effect). So it can be concluded that learning using the problem-based learning model has a high effect on the science learning outcomes of grade IV students of SDN 2 Rarang in the 2023/2024 school year.